Promoção do processo de resiliência em enfermeiras: uma possibilidade? - Belancieri, Maria de Fátima (2007)
Nurses, according to different studies, in their daily life, are submitted to a number of adversities by the conditions and organization of work which may break out stress and sickness symptoms. The purpose of this study is to investigate the possibility of promoting the resilience process in nurses at a university hospital, and specifically, to investigate their life quality and possible indicators of Nurses Resilience, as well as, to propose and evaluate a group intervention process as a possibility of providing resilience. Fifty one nurses of a university hospital have participated in the study. Although the research delineation has been qualitative, quantitative strategies have also been used, aiming the enhancement of the qualitative data. Quantitative data were collected by the Life Quality Scale (WHOQOL-bref) of WHO (WHOQOL GROUP test, 1998, FLECK and COLS, 1999), the RQ Test) from Reivich & Shatté (2002), as well as the socio-demographic data files. The quantitative data were collected by means of the focal group. The results analysis had as a theoretical referential the Social-Historic Psychology and the analysis technique, the signification nuclei proposed by Aguiar & Ozella (2006) who have assisted in the construction of a signification net, toward the proposed objectives. Thus, three nuclei emerged: the first named: I am a nurse, I never give up presented as the average for the emotions regulation factors, optimism, Causal analysis, empathy, self- efficacy and Exposition both in the pre-intervention and the post intervention: the second nucleus, Where is my energy? , is different from the first nucleus as to the Emotions Regulation and had scored under the average in pre and post intervention, and the third As Hardys: oh life, oh bad luck presented itself in all factors under the average, exception made to the Causal Analysis in which the score was in the average after the intervention. In the factor Impulses Control there was no difference between the three nuclei all of them scored above the average. Thus, the subjects of the first nucleus can be considered resilient subjects, the second, as going through a re(constructive) process, and the third, as extremely pessimistic, non resilient subjects deserving more attention by the Institution. As to the second objective of this study the promotion of the resilience process by group intervention process it was observed that it was not completely fulfilled which gives some indicators for further studies